Psychosocial factors associated with coping among women recently diagnosed HIV-positive during pregnancy - Kotzé, Marinda (AIDS Behav, 2013)
In order to identify the psychosocial factors related to the use of coping strategies by HIV-positive women diagnosed during pregnancy, four structured interviews were conducted over a period of two years with 224 HIV-positive women at antenatal clinics in Tshwane, South Africa. Two coping styles, active and avoidant coping, were assessed using an adapted version of the Brief COPE. Psychosocial variables associated with changes in coping over time were identified with mixed linear analysis. Increases in active coping were associated with decreasing levels of internalised stigma and depression, increasing self-esteem and positive social support, knowing someone who is living with HIV, being physically healthy and living above the poverty line. Increases in avoidant coping were associated with increasing internalised stigma and depression, lower levels of self-esteem, HIV-knowledge and lower levels of education. Recommendations are made for psychological support services to strengthen women’s ability to cope to enhance their health and that of their infants.